Logics for The Applied pi Calculus - Pedersen, Michael David (BRICS Report Series, 2006)
In this master’s thesis we present a modal logic for Applied pi which characterises observational equivalence on processes. The motivation is similar to that of Applied pi itself, namely generality: the logic can be adapted to a particular application simply by defining a suitable equational theory on terms. As a first step towards the logic for Applied pi, a strong version of static equivalence on frames is introduced in which term reductions are observable in addition to equality on terms. We argue that the strong version is meaningful in applications and give two refined definitions based on the notion of cores introduced in work by Boreale et al. for the Spi calculus. The refined definitions are useful because they do not involve universal quantification over arbitrary terms and hence are amenable to a logical characterisation. We show that the refined definitions coincide with the original definition of strong static equivalence under certain general conditions. A first order logic for frames which characterises strong static equivalence and which yields characteristic formulae is then given based on the refined definitions of strong static equivalence. This logic facilitates direct reasoning about terms in a frame as well as indirect reasoning about knowledge deducible from a frame. The logic for Applied pi is then obtained by adding suitable Hennessy-Milner style modalities to the logic for frames, hence facilitating reasoning about both static and dynamic properties of processes. We finally demonstrate the logic with an application to the analysis of the Needham-Schroeder Public Key Protocol.